An Analysis Of The Implementation Of The Erp-Sap System In Improving The Quality Of Coso-Based Accounting Information At Perum Jasa Tirta 1 Malang. - Ramadhani, Azzah Dzakiyah; Pusposari, Devy (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
This study aims to analyze the implementation of the ERP-SAP system to improve the accounting information quality of Perum Jasa Tirta I Malang. This study applies a qualitative method with a descriptive approach, in which information is collected through semi-structured interviews and direct observation of relevant staff in the accounting division. The analysis is based on COSO theory to evaluate internal controls that support ERP-SAP implementation in the context of accounting information quality, including aspects of relevance, reliability, comparability, verifiability, timeliness, and understandability. The results exhibit that the implementation of ERP-SAP results in a positive effect in terms of time efficiency, accuracy of financial reports, and the ability to make real-time data-based decisions despite the challenge in human resource (HR) adaptation that needs resolution to maximize the use of the system. Based on the findings, it is recommended that companies provide more training for employees and improve supervision mechanisms to ensure the effectiveness of the ERP-SAP system in producing accurate and timely information